La ética y el problema de Dios en Juan Luis Vives (1492-1540) - Alfonso Maestre Sánchez (Anales del Seminario de Historia de la Filosofía, 2003)
In the historical, turbulent and exciting times of the Renaissance Humanism, characterized by a return to classic Antiquity, and the renovation of all cultural manifestations, both philosophy and religion are affected from their very foundations. This scholastic crisis affects in such a way the conscience, of the individuals and the people that it demands a solution immediate although provisional solution, so that we continuing even the business of living. No wonder that among the ruins of tomist morality, some moralists arise, as that of Justus Lipsius (1547-1606), engased in renovating the stoic doctrines of Epicteto (ca. 50 to. of C. -125/138) and Séneca (ca. 4-65), and that of Pierre Gassendi (1592-1655), determined to Christianize Epicuro. For some could be a summarise of the Ethics of the Renaissance others believe that the first Ethics of modern philosophy should be considered to be a product of the Renaissance, even if it does not belong chronologically to it they meam Descartes (1596-1650), Spinoza (1632-1677) and Kant (1724-1804). However according to the opinion of some significant authors, we dont need to go back to Kant to find the authentic Ethics of the Renaissance. Juan Luis Vives published in 1524 a small booklet titled Introductio ad Sapientiam that for its internal ideological structure and its origin senequista and christan leaning occupies a privileged place within modern Ethic, and if we take accourt his content and chronology it can be considered as the Ethics of the Renaissance, at least of the Spanish Renaissance.